Effect of Digital Optimization Strategy and Communication on Employee Performance - Munandar, Dadang; Winantia, Marliana Budhinigtias; Narimawati, Umi (Universitas Bangka Belitung, 2024)
Digital transformation plays an important role as the organizational strategy, including bussiness sector. Digital transformation strategy is not only about digital technologies and markets transformation, however it impacts to capability of business to adapt for addressing sustainability and business challenges. This research aimed to analyze the effect of digital optimization strategy and communication on the employee performance. The research carried out quantitative approach and survey method involving 100 employees as respondents. The data analysis used Covariance Based Structural Equation Modeling (CBSEM) that was analyzed by Program LISREL ver 8.80. The research showed six results, namely (1) digital optimization strategy was categorized as moderate category, (2) communication was categorized as moderate category, (3) employee performance was categorized as very good category, (4) digital optimization strategy and communication affected significantly employee performance simultaneously, (5) digital optimization strategy affected significantly to employee performance partially, and (6) communication affected significantly to employee performance partially. The results indicated that digital optimization strategy and communication contribute positively on the employee performance which, in a certain time, can increase the company sustainability.